MULTI PERAN PEREMPUAN GENERASI SANDWICH DALAM MENJAGA KEHARMONISAN RUMAH TANGGA PERSPEKTIF MAQASHID SYARIAH - Fatimah Azzahra Pardiani; Muhsan Syarafuddin (USRAH: Jurnal Hukum Keluarga Islam, 2026)
Women are increasingly active in both public and domestic spheres in the modern family. This condition is driven by increasing family living costs, including the responsibility of supporting parents. Such circumstances are closely related to the “sandwich generation” phenomenon, which refers to individuals who simultaneously care for their parents and children. This study aims to identify the factors influencing the multiple roles of sandwich generation women and to analyze the contribution of Islamic values in maintaining household harmony. This research employs a descriptive  qualitative method. This study reveals that economic pressures are the primary factor underlying the multiple roles assumed by women within the sandwich generation. To maintain harmony within the household, sandwich generation apply various strategies, including practicing religious principles, maintaining open communication,  flexibility in role distribution, managing emotions, and resolving conflicts. Furthermore, an analysis based on maqashid al-shari’ah shows that the multiple roles performed by sandwich generation women are consistent with the objectives of Sharia, namely hifz al-din, hifz al-nafs, hifz al-mal, hifz al-‘aql, and hifz al-nasl. Normatively, these findings indicate that the multi-role practices of sandwich generation women align with the goals of Sharia in achieving benefit and preventing harm, thereby supporting household harmony.